Keniscayaan Perubahan Sistem Pengelolaan Sumber Daya Hutan di Jawa (Dari State Based menuju Community Based ) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
Javais facingcomplicatedemographic andecologicaplroblem.Therapid populationgrowthandthelackofnaturalresourcescausestructuralpovertyin village area.It is worsenedbythefactthatunemploymernatteincreasesw, aterdemands remainsgoingup,whilenaturacl apacityinfulfillingthoseneedsisdecreasingS. tatebasedForestmanagemenctonductedbyPerumPerhutansiincethreedecadesago hasnotgainedmaximumresultinsolvingthoseproblemsbecauseit emphasizeson timbepr roductionI.t isnecessartyochangetimbemr anagemenptaradigmwithanew paradigmwhichismorenaturallysustainableandabletogeneratepeople'seconomy. CommonPoolResource(CPR)analysisconcernswithfreepublicgood/ servicewhichcanbeaccessedbyanybodyofthecommunityand itsrighttouseit is equallydistributedto a wholememberof the community.CPRconceptcanbe implementetdo managemenotf state-ownedp,ublic-owneadndcommunityforest.. Howevers,everabl affiersarestillfacedbycommunity-basefodrestmanagemenint Java. CommunitFyorestryasanewparadigmin forestmanagemenctanonlybe establisheidn theseconditionst:heestablishemeonftpeople'ssupremacyc